A construção da personagem em narrativas literárias destinadas ao público infantil: em foco a montagem da cadeia referencial - Souza, Luciana Ribeiro de (2018)
This dissertation aims at verifying how the referential flux of texts written for children (more generally, “short stories” and “novels”) is conducted. The theoretical base upon which this study is constructed is that of Functionalism, examining grammar as an integration of the syntactic, semantic and pragmatic component (HALLIDAY, 1973, 1978, 1989; HALLIDAY; MATTHIESSEN, 2004; NEVES, 2004, 2007, 2010), and seen especially within the interactional process (DIK, 1997). This study also finds subsidiary support in textual linguistics, enunciation theory and cognitivism. Particularly it is pointed out the convenience of bringing attention to cohesive elements that participate in establishing reference in any utterance. However, considering that, currently, children’s books bring, in general, the verbal and the imagery interconnected, it is conducted an investigation on the interplay between linguistic referential organization and the non-verbal text. Furthermore, it is pertinent as a counterexample a sample of analysis of children’s texts from 19th century, which dispensed with the resource of illustration. The aims of this dissertation were to verify: (i) the different degrees of description and identification of the activated discourse object, seen in relation with the linguistic element used in the referential process (noun phrase, pronoun, zero), with special consideration of the proper noun and of the noun phrase with common nucleus; (ii) the relationship between the verbal and non-verbal text, with respect to the organization of the referential chain; (iii) comparatively the results about the two sets of texts under analysis; (iv) the possible pertinent contextual correlation to the interpretation of the data. The results of the present study, among other things, point to significant differences between current (20th Century) and past (19th Century) texts: a) the higher frequency of the use of proper names with illustrated texts; b) higher frequency of the use of noun phrase with a common noun as nucleus without the resource of illustration; c) differences in the establishment of the referential chain in illustrated texts. Overall, this research leads to the conclusion that contemporary children’s books are a form of art that, in uniting two distinct modalities of textual creation (verbal and illustrated text) in one whole editorial project, offers the readers (the children or the adult) the possibility of construing and reconstructing the same story, regarding the referential chain, through two paths of apprehension that the world of art offers: verbal an non-verbal text.